EFL Learners’ Responses to Teacher questions: A Case Study in an Indonesian Junior High School - Ana Maemanah; Agung Ginanjar Anjaniputra (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
This study looks at how teacher questioning methods influence classroom interaction in an English as a Foreign Language (EFL) situation. Its goal is to identify the types of questions used by teachers and to investigate how these questions shape interactional patterns during classroom conversation. Using a qualitative descriptive methodology, data were collected from classroom observations during three lessons, yielding 132 instructor questions. The data were transcribed, coded, and classified into four types: display questions, referential questions, procedural questions, and checking comprehension questions. The findings show that display queries were the most common and consistently produced short, predictable responses, resulting in interactional sequences that swiftly ended. Although allowed for more personalized responses they were not expanded through follow-up methods. Procedural and verifying comprehension questions were primarily used to manage classroom flow and confirm comprehension, with little contribution to interactional growth. Overall, classroom engagement was described as teacher-led, short, and with limited discourse expansion. According to the study, the efficiency of questioning is determined not only by the type of question employed but also by how teachers handle interactional sequences, which includes their ability to encourage student responses and facilitate deeper discussions. It proposes that more follow-up tactics should be used to generate more meaningful and student-centered classroom on their answers and facilitating peer discussions.